POLA EVALUASI PEMBELAJARAN JARAK JAUH PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM - Nurul Latifatul Inayati; Annas Fajar Rohmani; Armelya Puspita Ningrum (Universitas Muhammadiyah Surakarta, 2022)
The COVID-19 pandemic has changed the learning process, which requires learning to be done remotely. Likewise, the learning evaluation process is also carried out remotely. Evaluation is an important part of a learning process because with the evaluation of learning a teacher knows the weaknesses and strengths in the learning that has been done and can be used to monitor the progress of students. Moreover, Islamic religious education is something that is very much needed in social life, because being given Islamic religious education, can foster and guide students to be religious, moral, and dignified. The provision of Islamic religious education is also an effort to realize the goal of national education, namely having religious spiritual strength. This study aims to describe the pattern of evaluation of distance learning and the obstacles faced in evaluating distance learning in the subjects of Islamic Religious Education class VIII at SMP N 13 Surakarta and SMP N 1 Mojolaban. This research is a type of qualitative research, so that in conducting data analysis using qualitative descriptive analysis methods. As for the data collection using interviews, documentation, and observation. The results of this study found that the pattern of implementing distance learning evaluations in the cognitive, affective, and psychomotor domains had been carried out following the evaluation stages, namely planning, implementing, processing, and interpreting data, and reporting evaluation results. And for the obstacles faced during the evaluation of distance learning, namely in the cognitive realm, the test questions are only objective and there are no HOTS questions, so they are not effective in measuring children's understanding. Constraints in the affective domain cannot measure the value of attitudes in the social sphere. And for the psychomotor domain, the assessment is in the form of making practice videos, which makes students complain that there is no internet quota to send assignments because the average student system is in the middle to lower economy.